A COVID-19 Re-envisioned Teaching Practicum Curriculum - Carisma Nel; Carolina Botha; Elma Marais (Research in Social Sciences and Technology, 2021)
The changes taking place in the schooling landscape because of the coronavirus are real and meaningful and have implications for the training of preservice teachers, especially the teaching practicum component of their initial teacher education programs. The havoc caused by COVID-19 forced many faculties of education into a state of ‘panic-gogy’ to ensure that student teachers could complete their teaching practicums. In this paper we argue that consideration should be given to core teaching practices and practice-based teacher education pedagogies (i.e., representations and approximations) that can be used in alternative “placement contexts” that will supplement and harness the authenticity of school-based experiences. We provide two conceptual tools, collaboratively developed by teaching practicum educators and mentor teachers, that can be used as heuristic by other university-school partnerships when considering teaching practicum redesign efforts.